E. Cora Hind’s Feminist Thought: “The Woman’s Quiet Hour” in the Western Home Monthly, 1905–1922 - McKenna, Katherine (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2011)
E. Cora Hind was a turn of the 20th Century ‘First Wave’ feminist who has received little scholarly attention. This is remarkable, since in her time she was known world-wide as the agricultural editor of the Manitoba Free Press where she worked from 1901 until her death in 1942. This paper examines her column, “The Woman’s Quiet Hour” in The Western Home Monthly written from 1905 to 1922. The column provides a rich record of the thoughts of a self-educated intelligent feminist mind which defies easy categorization. Cora Hind was a staunch equity feminist, a union supporter and a resolute advocate for the single working girl. She also often expressed a conventional idealized view of the importance of maternal values. She was an ardent defender of the British Empire and immigrant assimilation, yet opposed discrimination and showed great appreciation of diverse cultural heritages. She was a leading member of conservative middle-class women’s organizations, yet her feminist views became so radical that they likely led to the abrupt end of her column. Hind was a complex and at times contradictory character whose social and political thought can teach us much about her own day as well as today’s feminist heritage.